Coeffcients of herdability and relatedness in a forest fragment of Araucaria angustifolia (Bertol.) Kuntze using genetic markers - Bueno da Silva, Erica Cristina [UNESP]; Kuboyama Kubota, Thaisa Yuriko [UNESP]; Teixeira de Moraes, Mario Luiz [UNESP]; Sebbenn, Alexandre Magno (Ipef-inst Pesquisas Estudos Florestais, 2015)
Methods based on genetic markers to estimate the coefficient of heritability in natural populations are important to understand the effects of natural selection on inheritance of quantitative traits. The objective of this study was to investigate the genetic control of the trait plant height in a fragmented population of Araucaria angustifolia. This study was conducted in a forest fragment of 5.4 ha of area, located in the State of Parana, Brazil. Estimates of heritability were performed using data from genotypes and height of regenerating individuals of the population. Four methods to estimate the relatedness between pairs of individuals (RITLAND, 1996; LYNCH; RITLAND, 1999; QUELLER; GOODNIGHT, 1989; WANG, 2002) for three distances (without criteria, 25 and 50 m) were used. The coefficient of heritability estimated using the estimator of relatedness of Ritland (1996), suggest that the genetic control of the trait height is low in the regeneration, thus the natural selection as well as the artificial selection have a low potential to change the mean of the population. The estimates based on the other methods to calculate the relatedness presented low precision, indication that these methods are not adequate for the data used.
Keywords: Araucaria Forest; Co-ancestry coefficient; Genetic parameter; Tree species